A Novel Double Fluorescence‐Suppressed Probe for the Detection of Hydrazine. Issue 48 (20th December 2019) - Li, Xue; Yin, Jiwei; Liu, Weiyan; Yang, Yutao; Xu, Wenzhi; Li, Wei
Abstract: Hydrazine is an important raw material in medicine and chemical industry. However, N2 H4 is very harmful to the environment and human body. Therefore, the detection of hydrazine is particularly important. In this report, a new type of fluorescence probe based on synergistic effect was developed for the detection of N2 H4 . The fluorescence of the probe was doubly inhibited by the PET (photo‐induced electron transfer) process and the bridled ESIPT (excited‐state intramolecular proton transfer) process. Upon addition of hydrazine, the interrupted PET process and restored ESIPT worked together leading to the fluorescence enhancement. The probe has good specificity for hydrazine. The LOD (limit of detection) was calculated to be 1.45 ppb (0.045 μM) and the linear range was 0.2‐40.0 μM. The contrast experiment showed that the synergistic effect could improve the sensitivity of the probe to hydrazine. In addition, the probe could be used for the quantitative determination of hydrazine in tap water. Abstract : A novel double fluorescence‐suppressed probe for hydrazine detection was developed. The probe based on synergistic effect showed high selectivity and sensitivity towards hydrazine. The LOD was of the probe to N2 H4 was 1.45 ppb (0.045 μM) with the linear range in 0.2‐40.0 μM, which is lower than the EPA standard (10 ppb). Moreover, the probe could detect hydrazine quantitatively in tap water.